Supramolecular chemistry : from concepts to applications - Kubik, Stefan (Berlin: De Gruyter, 2024)
This introductory textbook on supramolecular chemistry is a thoroughly revised and expanded version of the 1st edition, originally published in 2020. All chapters have been brought up to date and now include "Further Reading" sections that highlight relevant developments. In addition, a new chapter on supramolecular polymers has been added. With these changes, this book provides an even more comprehensive introduction to the exciting field of supramolecular chemistry than before. Readers will learn what forces hold supramolecular architectures together, how supramolecular systems are created and characterized, how molecular switches, motors, transporters, catalysts, chemosensors, and other functional systems work, and where supramolecular chemistry can play or already plays a role in our lives.
Includes index
Keywords: Chemical structure -- Molecular recognition; Nanostructured materials -- Chemistry$1 (BResearchs -- Chemistry$1 (BTechniques